PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBASIS PENILAIAN PORTOFOLIO TERHADAP KOMPETENSI PENGETAHUAN MATEMATIKA SISWA KELAS IV - Md Rai Advina Christianti (Indonesian Journal Of Educational Research and Review, 2018)
This study is aim to determine the effect of discovery learning model besed on portofolio of mathematies knowledge competencies of IV grade students of elementary school Gugus II Kuta Utara academic year 2017/2018. This research is an quasi experiment design with Nonequvalent Control Group Design. Population in this research were all students of IV elementary school Gugus II Kuta Utara academic year 2017/2018 as many as 277 students. The sample of this research is the IV grade student of elementary school No. 3 canggu as experimental class and IVC grade student of elementary school No. 1 Tububeneng as control class with the total of each group as much as 30 students after equalized by matching technique. The method of data collection in this research is test method, with the usual double choice test amount of 30 items that have been validity. The data analysis using t-test shows that there is were significant differences of students mathematics knowledge competency which is learned by using discovery learning model besed on portofolio and students who ware taught by using conventional learning in IV grade students of elementary school Gugus II Kuta Utara academic year 2017/2018. This is evidensed by the (thitung = 2,683 > ttabel = 2,021) at the significant of 5% with dk n1+n2-2 (30+30-2=56) and the average competency value of mathematics knowledge of students experimental group 73,50 and the average of competence value of mathematic knowledge of student control group 64,40. Thus, it can be concluded that the application of discovery learning model besed portofolio influence the knowledge competence of mathematics IV grade in elementary school Gugus II Kuta Utara academic year 2017/2018